Multiple mechanical and thermal blast injury in civilian industrial setting – possible parallel to the battlefield blast syndrome type injuries - Klein, Leo; Havel, Eduard; Šmejkal, Karel; Cerman, Jaroslav; Hošek, František; Hronek, Miloslav (Vojenské zdravotnické listy, 2011)
A 43-year-old man, injured during a factory explosion on January 4, 2010, was transported to the nearest hospital. Volume resuscitation started, subclavian vein cannulation, chest tube, and covering of burns were performed. The intubated and ventilated patient was transferred by helicopter to our hospital. The leading diagnoses were: haemorrhagic – traumatic and burns shock, haemoperitoneum, pneumothorax, subtotal amputation of the left distal crus/feet, burns over 40 % of the body surface, right calcaneus fracture etc. Preliminary circulatory stabilisation with discontinuation of norepinephrine infusion was achieved within 10 hours, by excessive positive fluid balance, which took three days (22, 10 and 9 litres). Preliminary blood lactate 7 mmol/l was normalised within 24 hours. Blood albumin level 15 g/l was tolerated without any artificial replacement. The second hit appeared on day 10, in a form of septic shock caused by Aspergillus fumigatus infection from the lacerated left lower limb. High-volume continuous haemodiafiltration because of hyperpyrexia was used, after the exarticulation in the left knee-joint. An excessive proteolysis (urea loss more than 1000 mmol/day) persisted 1.5 months, with energy expenditure over 2600 kcal/day. The patient underwent multiple surgical interventions. Metabolic support using combined parenteral and enteral nutrition was performed during the first month, enteral nutrition combined with food were consequently given for more than 3 months. The patient was hospitalised until April 26, 2010. These types of traumas are fully comparable with military battlefield environment injuries. Principles of war surgery (life and limb saving, damage control surgery) should be applied also in civilian environment, particularly in disaster situations.
Keywords: Nutritional Support; Aspergillus fumigatus; Humans; Shock, Traumatic; umělé dýchání; Respiration, Artificial; rány a poranění; krvácení; hemoperitoneum; Critical Care; péče o pacienty v kritickém stavu; Pneumothorax; lidé; financování organizované; Foot; Explosions; pracovní úrazy; nutriční podpora; Burns; Spleen; Traumatology; pneumotorax; Trauma Centers; Tibial Fractures; Hemoperitoneum; Financing, Organized; Occupational Injuries; traumatický šok; fraktury tibie; Male; Wounds and Injuries; Wound Infection; traumatologie; Adult; infekce v ráně; exploze; dospělí; polytrauma; amputace; noha (od hlezna dolů); Multiple Trauma; traumatologická centra; popálení; Shock, Septic; mužské pohlaví; arteriae tibiales; Tibial Arteries; septický šok; slezina; Hemorrhage; Amputation, Surgical